All Aboard the Moonlight Train - Crow, Kristyn; Won, Annie (New York : Doubleday Books for Young Readers, 2020)
On board the Moonlight Train, sleepy readers explore the jungle deep where beasts and critters creep.
Keywords: Jungle animals -- Juvenile fiction; Railroad trains -- Juvenile fiction; Bedtime -- Juvenile fiction; Stories in rhyme; Jungle animals -- Fiction; Railroad trains -- Fiction; Bedtime -- Fiction